Delayed Graft Function in Simultaneous Liver Kidney Transplantation. Issue 3 (March 2020) - Weeks, Sharon R.; Luo, Xun; Haugen, Christine E.; Ottmann, Shane E.; Gurakar, Ahmet O.; Naqvi, Fizza F.; Alqahtani, Saleh A.; Philosophe, Benjamin; Cameron, Andrew M.; Desai, Niraj M.; Segev, Dorry L.; Garonzik Wang, Jacqueline M.
Abstract : Background: Delayed graft function (DGF) is associated with inferior posttransplant outcomes in kidney transplantation. Given these adverse outcomes, we sought to determine the incidence, unique risk factors, and posttransplant outcomes for simultaneous liver kidney (SLK) transplant recipients developing DGF. Methods: We studied 6214 adult SLK recipients from March 2002 to February 2017 using the Scientific Registry of Transplant Recipients. We determined associations between risk factors and DGF using Poisson multivariate regression and between DGF and graft failure and mortality using Cox proportional hazard analysis. Results: The overall rate of DGF was 21.8%. Risk factors for DGF in the hepatitis C virus (HCV)-negative recipient population included pretransplant dialysis (adjusted incident rate ratio [aIRR] 3.26, P = 0.004), donor body mass index (aIRR 1.25 per 5 kg/m 2, P = 0.01), and transplantation with a donation after circulatory death (aIRR 5.38, P = 0.001) or imported donor organ (regional share aIRR 1.69, P = 0.03; national share aIRR 4.82, P < 0.001). DGF was associated with a 2.6-fold increase in kidney graft failure (adjusted hazard ratio [aHR] 2.63, P < 0.001), 1.6-fold increase in liver graft failure (aHR 1.62, P < 0.001), and 1.6-fold increase in mortality (aHR 1.62, P < 0.001). Conclusions: In HCV-negative SLK recipients, recipient pretransplant dialysis and components of kidney graft quality comprise significant risk factors for DGF. Regardless of HCV status, DGF is associated with inferior posttransplant outcomes. Understanding these risk factors during clinical decision-making may improve prevention of DGF and may represent an opportunity to improve posttransplant outcomes.